Regional Volume Tables of Dipterocarpus tuberculatus Roxb. (Based on the Data of Manipur State) - Sharma, R. P.; Jain, R. C. (Indian Forester, 1978)
Volume tables of I>Dipterocarpus tuberculatus have been prepared by the method of linear regression. The model used is V=a+bD2H. Tables based on this model have been given.